The knowledge management in intensive environments of knowledge: the small incubated softwares companies (Journal of Information Systems and Technology Management, 2009)
This article discusses the understanding and behavior of entrepreneurs incubated for software companies (development of information systems, provide services in information technology - hardware and software, and advise on the implementation of administrative management systems) in relation to knowledge, in the obtaining and facilitating the use of knowledge and availability of media. Initially, it sought a fundamental concept for the study and is based contextualise the issue, making the connection with the knowledge of the views of academic and business. After an analysis was conducted based on applied research to executives on their understanding of the concept of knowledge regarding the way in which it operates (professional and personal), concluding with the importance of knowledge for business growth from the person.